Bargaining with Patriarchy?: Women Pentecostal leaders in Zimbabwe - Mapuranga, Tapiwa Praise (Fieldwork in religion, 2013)
The status of women remains contested. While women constitute the majority of members in literally all religions, the top positions tend to be monopolised by men. An array of historical, cultural, theological and socio-economic reasons has been proffered to account for this anomaly. New religious movements have often promised women liberation and emancipation. In Africa, Pentecostal and neo-Pentecostal movements have accorded women leadership roles as they interrogate missionary Christianity. This study examines women's notable rise to influential leadership within the Pentecostal movement in Zimbabwe. While the older Pentecostal churches of the 1970s and 1980s were male dominated, the 1990s ushered in the phenomenon of women leaders within the Pentecostal movement in Zimbabwe. Notable examples include Apostle Eunor Guti, Apostle Petunia Chiriseri, Dr Faith Wutawunashe and others. However, these women Pentecostal leaders tend to be married to charismatic founders of Pentecostal ministries. This study interrogates their status within the Pentecostal movement. On the hand, it contends that these women must be accepted as leaders in their own right. It argues that they have appropriated the religious significance of women in indigenous culture and have applied it to the Pentecostal movement. They are leaders of specific ministries and are not mere appendages of their husbands. However, on the other hand, the study argues that their position as wives of Pentecostal leaders needs to be approached critically. It has tended to generate a moderate position on feminist issues within the Pentecostal movement. The study concludes that women Pentecostal leaders in contemporary Zimbabwe tend to bargain with patriarchy. They are unwilling to challenge patriarchy and promote a biblical hermeneutics that is subservient. It suggests that gender within the Pentecostal movement in contemporary Zimbabwe requires a liberating biblical hermeneutics.